Considerations for the clinical use of contrast agents for cellular MRI in regenerative medicine. (November 2013) - Modo, Michel; Kolosnjaj‐Tabi, Jelena; Nicholls, Francesca; Ling, Wen; Wilhelm, Claire; Debarge, Olivier; Gazeau, Florence; Clement, Olivier; Aime, Silvio; Muller, Robert N.
<x xml:space="preserve">Abstract</x> Advances in regenerative medicine are rapidly transforming healthcare. A cornerstone of regenerative medicine is the introduction of cells that were grown or manipulated in vitro. Key questions that arise after these cells are re‐introduced are: whether these cells are localized in the appropriate site; whether cells survive; and whether these cells migrate. These questions predominantly relate to the safety of the therapeutic approach (i.e. tumorigenesis), but certain aspects can also influence the efficacy of the therapeutic approach (e.g. site of injection). The European Medicines Agency has indicated that suitable methods for stem cell tracking should be applied where these methods are available. We here discuss the European regulatory framework, as well as the scientific evidence, that should be considered to facilitate the potential clinical implementation of magnetic resonance imaging contrast media to track implanted/injected cells in human studies. Copyright © 2013 John Wiley & Sons, Ltd.